The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1099/00222615-47-6-499
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of cases of infections due to Aeromonas hydrophila revealed by combined RAPD and ERIC-PCR

Abstract: Two polymerase chain reaction (PCR)-based methods were used for epidemiological typing of Aeromonas hydrophila. Random amplification of polymorphic DNA (RAPD) and enterobacterial repetitive intergenic consensus-PCR (ERIC-PCR) were applied to an outbreak involving seven patients. The epidemiological situation appeared complex; with the exception of two clinical isolates, all gave unique patterns with both techniques. These methods demonstrated nosocomial transmission in one unit and permitted the study to exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 22 publications
3
26
0
1
Order By: Relevance
“…The majority of isolates were genetically distinct (62% of the isolates had similarities below 90%), with no dominant clones of A. veronii associated with MAS in the fish population investigated. This kind of high genetic diversity had been observed among clinical and environmental isolates of aeromonads from different sources typed by the above technique (Davin-Regli et al 1998, Szczuka & Kaznowski 2004.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of isolates were genetically distinct (62% of the isolates had similarities below 90%), with no dominant clones of A. veronii associated with MAS in the fish population investigated. This kind of high genetic diversity had been observed among clinical and environmental isolates of aeromonads from different sources typed by the above technique (Davin-Regli et al 1998, Szczuka & Kaznowski 2004.…”
Section: Discussionmentioning
confidence: 99%
“…ERIC-PCR ®ngerprinting which has previously been used to type enterobacteria and mycobacteria (Guerrero et al 1995;Sechi et al 2000a) was applied to differentiate the Aeromonas strains in this study. Davin-Regli et al 1998) distinguished between A. hydrophila strains by using RAPD and ERIC-PCR. Faeces/99…”
Section: Phenotypic Testsmentioning
confidence: 99%
“…Studies in France also found that the water sampled in the hospital was not the source of infections for patients at the University Hospital in Marseille (18). With the high prevalence of HIV and AIDS in South Africa, patients might become more susceptible to infection by Aeromonas, and the possibility of acquiring the organisms from water is high and represents a great threat to human health.…”
Section: Discussionmentioning
confidence: 98%